1256 Orthopaedics and The COVID19 Pandemic: Was Achilles Just A "Weekend Warrior"?. (12th October 2021) - Murphy, B; Hurson, C
Abstract: Background: The COVID19 pandemic has affected the types of trauma being operated on by Orthopaedic surgeons. Lifting of restrictions pertaining to sports saw a sudden return to play for many people after a period of inactivity. Achilles tendon ruptures are associated with these episodic athletes. In our institution, we appeared to have a large number of these injuries within a short space of time. We hypothesised that Phase 3 of "Lockdown", where all sports were allowed to return, led to increased Achilles tendon rupture rates vs. the same period in 2019 due to a prolonged period of inactivity. Method: Data from electronic theatre logbooks of all operations performed in the trauma theatre from 27 th March 2020 (Lockdown begins) to 31 st July 2020 and 27 th March 2019 to 31 st July 2019 was collected. Results: 772 cases were performed in 2019. There were 17 Achilles tendon ruptures in that period (2.2%). 14 of these occurred after Phase 3. 555 cases were performed in 2020. There were 13 Achilles tendon ruptures in that period (2%). 11 of these occurred after Phase 3. Conclusions: Overall, there was a greater number and greater rate of Achilles tendon ruptures in 2019 vs. the equivalent "Lockdown" period in 2020. 8 of the 11 occurring after Phase 3 in 2020 occurred in the month of July. This led the authors to believe they were occurring more frequently. In conclusion, the COVID19 pandemic restrictions and subsequent return to play after inactivity does not increase the rate of Achilles tendon rupture.